PD-L1+ and XCR1+ dendritic cells are region-specific regulators of gut homeostasis - Thais G. Moreira (Nature Portfolio, 2021)
Dendritic cells initiate and regulate adaptive immunity and differ according to gut anatomical location. Here the authors show that DC residing in the upper and lower intestines show differential PD-L1 and XCR1 expression and drive specific T cell responses to prevent gut inflammation.